The impact of employee motivation on organisational performance in the case of NOSA company - A. J. Bonyani (Управление)
The article investigates the features of employee motivation impact on the organisation effectiveness. The purpose of the study is to clarify the theoretical foundations of motivation, improve the methodological approaches and substantiate the practical recommendations concerning the motivational mechanism development, which is one of the most important components in the chain of achieving high performance of modern business entities. Research objectives are to analyse the of employee motivation impact on the effectiveness of the organisation, identify and evaluate the relationship between the impact of the remuneration system on the results of the organisation’s activities, formulate recommendations to firms and their managers on promoting the system of motivation and remuneration of employees, that expands the effectiveness of the organisation.In the article the terminological analysis of the definition of “employee motivation” has been carried out. The relationship between employee motivation and the remuneration system with organisational efficiency has been formalised. The effectiveness of the motivation system and the employee incentive system at Iran software and hardware company (NOSA) has been evaluated using the questionnaire and expert survey method. The relationship between the productivity of the company’s personnel and the level of remuneration has been ascertained using the correlation and regression analysis. The recommendations to improve the efficiency of the labor motivation system at the NOSA enterprise have been formulated based on the obtained data.The results obtained allowed us to conclude that the interaction of motives and incentives is the tool that allows us to meet the needs of the employee in the most appropriate way for him – as a result of the realization of his abilities. Study of the motivation system at the NOSA enterprise indicates that the staff is not satisfied with the material remuneration. The company’s management during developing directions for improving the motivation program should take into account that the growth rate of labor productivity should outstrip the growth rate of its remuneration, otherwise the company’s resources will be spent inefficiently.